Generation of packaging cell lines for pseudotyped retroviral vectors of the G protein of vesicular stomatitis virus by using a modified tetracycline inducible system. - Chen, S T (1996)
We have previously shown that the G protein of vesicular stomatitis virus (VSV-G) can be incorporated into the virions of retroviruses. Since expression of VSV-G is toxic to most mammalian cells, development of stable VSV-G packaging cell lines requires inducible VSV-G expression. We have modified the tetracycline-inducible system by fusing the ligand binding domain of the estrogen receptor to the carboxy terminus of a tetracycline-regulated transactivator. Using this system, we show that VSV-G expression is tetracycline-dependent and can be modulated by beta-estradiol. Stable packaging cell lines can readily be established and high-titer pseudotyped retroviral vectors can be generated upon induction of VSV-G expression.